2000
DOI: 10.1007/s001340000684
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of ultrasonography and cholescintigraphy to the diagnosis of acute acalculous cholecystitis in intensive care unit patients

Abstract: Sensitivity of US and MC, respectively, was 50% and 67%, specificity 94% and 100%, positive predictive value 86% and 100%, negative predictive value 71% and 80%, and accuracy 75% and 86%. The correlation between US and MC findings was 71%, with chi = 0.31. By Bayesian analysis the probability of disease if the MC finding was positive was 100% regardless of US results. A positive US finding was associated with a 86% probability of disease, but with a probability of only 66% in case of negative MC results. MC is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 26 publications
1
25
0
3
Order By: Relevance
“…Morphine augmentation can enhance the specificity of scintigraphy. 8 Establishing the diagnosis of AAC as early as possible is important, because delay in treatment is associated with high risk for gallbladder perforation or gangrene. 2,6 The recommended treatment of AAC is immediate hemodynamic stabilization and initiation of broad spectrum antibiotics providing coverage for enterococci, Gram-negative bacilli, and anaerobes, 3 followed by prompt percutaneous cholecystostomy.…”
Section: Discussionmentioning
confidence: 99%
“…Morphine augmentation can enhance the specificity of scintigraphy. 8 Establishing the diagnosis of AAC as early as possible is important, because delay in treatment is associated with high risk for gallbladder perforation or gangrene. 2,6 The recommended treatment of AAC is immediate hemodynamic stabilization and initiation of broad spectrum antibiotics providing coverage for enterococci, Gram-negative bacilli, and anaerobes, 3 followed by prompt percutaneous cholecystostomy.…”
Section: Discussionmentioning
confidence: 99%
“…Duplicate entries, cases of calculous cholecystitis or other biliary pathology were excluded from the study. We included all patients who on either ultrasonography (US) or CT imaging were found to have AAC with gall bladder wall thickness greater than 3 mm, periocholecystic fluid, subserosal oedema, intramural gas or sloughed mucosal membrane [2,12,[16][17][18][19][20][21]. Patients were required to satisfy at least 2 of these major criteria in the absence of biliary calculi and have AAC verified by the reporting radiologist.…”
Section: Methodsmentioning
confidence: 99%
“…134 A prospective study comparing ultrasonography and morphine cholescintigraphy (MC) in the diagnosis of AAC found that the sensitivities of ultrasonography and MC were 50% and 67%, specificities were 94% and 100%, positive predictive values were 86% and 100%, negative predictive values were 71% and 80%, and accuracies were 75% and 86%, respectively. 135 Combining both ultrasonography and cholescintigraphy may lead to greater diagnostic accuracy.…”
Section: Imaging Ultrasonographymentioning
confidence: 99%